2019
DOI: 10.1111/crj.13060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among different presentations of venous thromboembolism because of lung cancer

Abstract: Introduction Venous thromboembolism (VTE) because of lung cancer has been sufficiently studied, nevertheless, little is known regarding the discrepancy of clinical characteristics and predictive factors among different presentations of VTE because of lung cancer. Objectives This study was designed to investigate the distinction of clinical characteristics and predictive factors among different presentations of VTE because of lung cancer. Methods All patients concomitant lung cancer and VTE were stratified into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A recent cohort study has shown that 9.23% of patients with lung cancer had a diagnosis of VTE ( 11 ). The incidence of thrombosis is as high as 13.6% throughout non-small cell lung cancer cases ( 11 ) and the lung adenocarcinoma accounts three-fold higher than squamous cell carcinoma, which may be attributed to increased mucin ( 12 ). The pathogenesis of cancer-associated thrombosis is multifactorial and involves all aspects of Virchow’s triad.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cohort study has shown that 9.23% of patients with lung cancer had a diagnosis of VTE ( 11 ). The incidence of thrombosis is as high as 13.6% throughout non-small cell lung cancer cases ( 11 ) and the lung adenocarcinoma accounts three-fold higher than squamous cell carcinoma, which may be attributed to increased mucin ( 12 ). The pathogenesis of cancer-associated thrombosis is multifactorial and involves all aspects of Virchow’s triad.…”
Section: Discussionmentioning
confidence: 99%
“…The Khorana score is the most classic, authoritative, and long-tested VTE risk assessment score, in which a total score > 2 represents a high risk of VTE [ 11 ]. Lung cancer patients with metastatic disease status are nearly 3 times likely to develop VTE, in contrast to those with non-metastatic status [ 23 , 24 ]. In a study with respect to venous thrombosis in resected specimens for non-small cell lung cancer (NSCLC), 53.6% of cases with thrombosis were accompanied by tumor vascular infiltrating [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 Interestingly, elevated CEA levels has been associated with an increased risk for the development of PE. 16,18 Of the histologic variants, lung adenocarcinoma is the lung cancer histopathology most associated with the later development of VTE. 16 Other important risk factors that were associated with increased prevalence of VTE in patients with lung cancer were the presence of distant metastasis, leukocytosis, and younger age.…”
Section: Lung Cancer and Vtementioning
confidence: 99%